Emotional Literacy Training Using Role-Playing Techniques for Junior High School Students - Sitti Riadil Janna; Syahril Syahril (AL-ISHLAH: Jurnal Pendidikan, 2024)
The ability to recognize and effectively communicate emotions, referred to as emotional literacy, is crucial for interpersonal success and psychological health. This study aimed to enhance the emotional literacy of adolescents in junior high school through the application of role-playing techniques within guidance and counseling services. Employing a quantitative methodology, this research adopted a pretest-posttest experimental design to evaluate the effectiveness of these interventions. A total of eight respondents participated in the study. The emotional literacy scale served as the primary instrument for measuring changes in emotional literacy levels. Data were analyzed using the non-parametric Wilcoxon signed-rank test. The findings revealed that role-playing significantly improved the emotional literacy of the participants. These results have important implications for school counselors, suggesting that incorporating role-playing techniques into counseling sessions can be an effective strategy for fostering emotional development among students. This research underscores the potential of targeted educational interventions in enhancing emotional literacy, which can contribute to better emotional management and healthier adolescent development.